PEMANFAATAN LIMBAH PETERNAKAN DALAM KONSEP PERTANIAN TERPADU GUNA MEWUJUDKAN PERTANIAN YANG BERKELANJUTAN - Suryono, Suryono; Dewi, Widyatmani Sih; Sumarno, Sumarno (Caraka Tani - Jurnal Ilmu Ilmu Pertanian, 2014)
Utilization of farm wastes in order to realize the concept of integrated farming is a sustainable agriculture community service program in cooperation with two partners , namely : ( 1 ) quail - catfish Breeders Agribird , and ( 2 ) dairy farms and agricultural businesses